2020
DOI: 10.3390/medicina56110613
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Discharge Predictors of 1-Year Rehospitalization in Adolescents and Young Adults with Severe Mental Disorders: A Retrospective Cohort Study

Abstract: Background and objectives: Readmissions of youths hospitalized for a severe mental disorder are common events and bear a remarkable human, social, and economic burden. The current study aimed at evaluating predictors of 1-year rehospitalization in a sample of adolescents and young adults with severe mental disorders. Materials and Methods: Data for ≤25-year-old inpatients with a severe mental disorder and consecutively admitted between 1 January 2016 and 30 June 2019 were collected. Subjects were retrospective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 41 publications
1
12
0
Order By: Relevance
“…Among them, alcohol use disorder (AUD) is one of the most frequent, involving about one quarter of individuals suffering from BD [ 3 ]. The comorbidity between AUD and BD leads to worse clinical outcomes, possibly characterized by poor response to treatment [ 4 ], mood instability and greater symptom severity [ 5 ], increased suicidality [ 6 ], heightened risk of hospitalization [ 7 , 8 ], and cognitive dysfunctions [ 9 ]. Among different clinical correlates perhaps explaining this comorbidity, a role for ADHD, which is, in turn, a frequent co-occurring condition in BD [ 10 , 11 ], can be hypothesized.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, alcohol use disorder (AUD) is one of the most frequent, involving about one quarter of individuals suffering from BD [ 3 ]. The comorbidity between AUD and BD leads to worse clinical outcomes, possibly characterized by poor response to treatment [ 4 ], mood instability and greater symptom severity [ 5 ], increased suicidality [ 6 ], heightened risk of hospitalization [ 7 , 8 ], and cognitive dysfunctions [ 9 ]. Among different clinical correlates perhaps explaining this comorbidity, a role for ADHD, which is, in turn, a frequent co-occurring condition in BD [ 10 , 11 ], can be hypothesized.…”
Section: Introductionmentioning
confidence: 99%
“…We measured the reliability in the form of internal consistency expressed as Cronbach's alpha coefficient where a cut-off of ≥0.70 was considered acceptable. We assessed the face and content validities during the translation and back-translation stages (19). Construct validity was assessed by performing the factor analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Suicidal ideation may indicate mental health problem, risky sexual and criminal behaviors which consume health services (18). One study identified that suicidal attempt is an important predictor for readmission among youths with severe mental illness (19). Psychometrically valid scales in native languages would help to identify the mental events of suicidal behavior, promote research and better mental health services as well (20,21).…”
Section: Introductionmentioning
confidence: 99%
“…First, research in high-risk populations, such as children in residential care and those leaving the care systems – is strongly needed as results across the entire spectrum of adversity exposure may not generalize to the top end of the spectrum. Adding psychoneuroendocrinological stress-measures to such studies or to routine care in the long run might help to better predict adverse outcomes in the long run as for instance rehospitalization in those with history of adversity or severe mental illness ( Bartoli et al, 2020 ). Second, clearer agreed-upon conceptualization and comprehensive measurement of adversity and stressors is needed to move the field forward, this should include incorporation of non-invasive biological measures of stress such as hair cortisol to expand the stress-phenotype measured ( Crosswell and Lockwood, 2020 ; Epel et al, 2018 ; McLaughlin, 2016 ).…”
Section: Discussionmentioning
confidence: 99%